(untitled) (Scientific journal of the Fergana State University, 2024)
The article defines the term ‘control’ and describes its role in the educational process. The goals and objectives of control are described and it is established that the goals of control are to determine the achievement and success of students, the level of mastery of knowledge, skills and abilities provided for by the program in the subject, teaching students methods of mutual control and self-control, nurturing in students such personality traits as responsibility for the work performed, showing initiative. During the theoretical study, the basic principles of organizing student knowledge control were formulated. It was found that the basic principles of control are focus (compliance with the goals of the curriculum), objectivity (to prevent subjective assessment), regularity (constant or repeated control), efficiency (serves for the full implementation of functions), hierarchical organization (phasing), complexity and consistency (planfulness).